Requirement engineering for Kantin Online system / Diyana Halim Khoo - Halim Khoo, Diyana (2016)
The schools in Malaysia are equipped with a canteen that offered food for the children to purchase during their recess. The current issues gathered from the past studies and newspaper specially had indicated that the food provided are not healthy and expensive compared with the quantity and quality provided. A preliminary study of families with parents working in urban areas such as the Klang Valley had been conducted in order to understand their satisfaction and awareness of the food purchased by their children at the school canteen. It had resulted that parents are concerned with the food purchased by their children at the school canteen, especially the primary school children. Most of the parents do not know what their children had been buying and eating at the school canteen currently. Getting enough food, if possible a healthy and nutrition is very important for children so that their performance in school will not be disturbed or drop. This had led to this research by gathering the requirement engineering for a system called Kantin Online. It is an online system that runs through the web that monitors children food purchase in schools. In order to gather the requirement engineering, this research needs to understand how the school canteen in the primary school manage their operations. Interview and observation were done with the canteen operator and school while questionnaire was distributed within the parents in Klang Valley. From the result of interview, observation and questionnaire, this research had listed the requirement engineering for Kantin Online and translated these requirements into a prototype where it had been evaluated by the HCI experts through Heuristic Evaluation. Although a lofidelity prototype had been developed, it has managed to gather user requirements with the experts' feedback helping to enhance the features further. Kantin Online has the potential to help parents manage their child's food intake but this requires further studies.